Coordination Interactions in the Crystalline Lattice of Alkaline Ions with the Polyoxometalate [V12b18o60h6]10- Ligand - Costamagna-Martra, J; Costamagna-Martra, J; Venegas-Yazigi, D; Venegas-Yazigi, D; Hermosilla-Ibanez, P; Hermosilla-Ibanez, P (Taylor and Francis Ltd., 2014)
In the present work, the synthesis and structural characterization of two new polyoxovanadoborate (BVO) frameworks, based on the [V12B18O60H6]10- polyanion, are reported, K(H3O)(enH2)4[V12B18O60H6]·9.60H2O(1) and Li8(NH4)2[V12B18O60H6]·8.02H2O (2). Both compounds are obtained in a mixed valence ratio of 10VIV/2VV. Framework 1 is characterized by potassium ions coordinated by the BVO cluster and ethylenediammonium and hydronium ions as charge-compensating agents. In framework 2, the BVO clusters are coordinating lithium ions and the charge is compensated by ammonium ions. Using the SHAPE 2.1 program, it was possible to calculate the best geometry for the existing lithium and potassium ions. For 2, the lithium ions are five-coordinate, best described by a square pyramid (SPY-5), while the coordination sphere around the potassium ions in 1 are six-coordinate. For 1, the coordination sphere of the existing potassium ions in the framework can be described as trigonal prism (TPR-6). Calculations were also done for a previously reported cluster [Na10[(H2O)V12B18O60H6]·18H2O] (3), in which the sodium ions are six-coordinate but in two different geometries, these being octahedral and TPR-6. The influence of the interactions of the alkali ions with the [V12B18O60H6]10- polyanion, on the vanadate and borate absorption bands observed in the infrared spectra, is discussed. © 2014 Taylor & Francis.
Keywords: Polyoxometalate; Mixed valence; BVO; Lithium; V12B18O60